Utility Regulation : A Critical Path for Revising Price Controls - Green, Richard (World Bank, Washington, DC, 2012)
The United Kingdom has pioneered the use of price control regulation. The periodic review of these controls lies at the core of the mechanism, and the UK experience shows that this review is complex and time-consuming and can be controversial. Based on the UK experience the author proposes a sequence of tasks that regulators in other countries could use when revising price controls. He argues that regulators should start to reset controls at least two years before new controls are due to come into effect. Much information will be required, and it will all have to be checked and processed before the regulator can propose new controls. In addition, most regulatory systems include an appeals mechanism to protect companies against overly zealous regulators, so regulators must make their proposals early enough to allow for a possible appeal. These considerations imply that regulators should make their proposals at least nine months before new controls are due to take effect, to allow six months for an appeal and time to implement the eventual decision.